Analisis Manajemen Risiko Bencana Banjir Bandang di Pasar Sarulla Tahun 2024 - Yolanda Agnesia Sinurat; Aldri Frinaldi (YASIN, 2026)
Flash floods are hydrometeorological disasters that frequently occur in Indonesia and have serious impacts on communities, infrastructure, and economic activities. Although flood disaster risk management has been widely studied, research specifically examining flash flood risk management in Pasar Sarulla, Tapanuli Utara Regency, in 2024 remains limited. This study aims to analyze the causal factors, impacts, and community-based mitigation strategies for addressing the disaster. This study employed a qualitative approach with a literature study design. Data were collected through the documentation of government reports, scientific journal articles, official publications of the National Disaster Management Agency, local government reports, and reports from credible online media. The data were analyzed using content analysis through the stages of reduction, presentation, interpretation, and conclusion drawing. The results showed that the flash flood was triggered by the interaction of extreme rainfall, watershed degradation, sedimentation, poor drainage systems, and the high vulnerability of settlements near river channels. The disaster caused damage to residential houses, public facilities, transportation infrastructure, and commercial buildings and disrupted the community’s economic activities. This study concludes that effective flash flood risk management requires the integration of structural and nonstructural mitigation, active community involvement, environmental rehabilitation, and the strengthening of disaster management institutions. Theoretically, the findings contribute to the development of community-based disaster risk management studies, while practically, they can serve as a basis for local governments to improve preparedness, strengthen early warning systems, rehabilitate watersheds, and implement spatial planning based on disaster risk reduction.